Does coprescribing nonsteroidal anti‐inflammatory drugs and oral anticoagulants increase the risk of major bleeding, stroke and systemic embolism?. Issue 11 (8th June 2022) - Penner, Leonie S.; Gavan, Sean P.; Ashcroft, Darren M.; Peek, Niels; Elliott, Rachel A.
Abstract : Aims: To examine the risk of gastrointestinal (GI) bleeding, major bleeding, stroke and systemic embolism associated with prescribing nonsteroidal anti‐inflammatory drugs (NSAIDs) to adults receiving oral anticoagulant (OAC) therapy. Methods: We conducted a population‐based cohort study in adults receiving OAC therapy using linked primary care (Clinical Practice Research Datalink GOLD) and hospital (Hospital Episodes Statistics) electronic health records. We used cause‐specific Cox regression models with time‐dependent NSAID treatment in a propensity score matched population to estimate the increased risk of GI bleeding, stroke, major bleeding and systemic embolism associated with NSAID use. Results: The matched cohort contained 3177 patients with OAC therapy alone and 3177 with at least 1 concomitant NSAID prescription. Compared with OAC therapy alone, concomitant prescription of NSAIDs with OACs was associated with increased risk of GI bleeding (hazard ratio [HR] 3.01, 95% confidence interval [CI] 1.63 to 5.55), stroke (HR 2.71, 95% CI 1.48 to 4.96) and major bleeding (HR 2.77, 95% CI 1.84 to 4.19). The association with systemic embolism did not reach statistical significance (HR 3.02, 95% CI 0.82 to 11.07). Sensitivity analyses indicated that the results were robust to changes in exclusion criteria and the choice of potential confounding variables. Conclusion: When OACs are coprescribed with NSAIDs, the risk of adverse bleeding events increases and, simultaneously, the protective effect of OACs to prevent strokes reduces. There is a need for interventions that reduce hazardous prescribing of NSAIDs in people receiving OAC therapy.